Comparative Analysis of the Influence of PV Bus Representation in the Current Injection Continuation Power-Flow - Oliveira, C. C. [UNESP]; Minussi, C. R. [UNESP]; Alves, D. A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2018)
This paper presents a comparative analysis of different voltage controlled bus (PV bus) representations and their influence in the convergence of Newton-Raphson continuation power-flow based on current injection formulation written in polar coordinates. The continuation power-flow methods developed with these different representations were applied to trace the P-V curve of IEEE tests systems and of two realistic Brazilian systems of 638 and 787 buses, corresponding to parts of the South-Southeast Brazilian system. The obtained results show an improvement in the performance of the current injection continuation power flow method obtained by a new representation.
Keywords: Continuation method; maximum loading point; Newton-Raphson power flow; P-V curve; PV bus representation